Khālid al-Kātib in the Biographical Tradition - Tobkin, Jennifer (Journal of Abbasid Studies, 2023)
Khālid al-Kātib is the author of more than 500 love poems and was associated with several notables of the Abbasid court, including Ibrāhīm b. al-Mahdī. Male-male love is a major theme in Khālid’s poetry and akhbār. Abū Tammām figures prominently in the biographical anecdotes about Khālid, both as an admirer and an adversary. Khālid’s akhbār in Kitāb al-Aghānī, Taʾrīkh Baghdād, and other sources provide insights into his relationships with his contemporaries while leaving open many questions about life, love, and poetry in Abbasid Baghdad.